Dampak Pemberhentian Guru Terhadap Sekolah - Tiara Lubis; Farras Fadhillah; Muhammad Chaidir; Tengku Darmansah (Student Research Journal, 2024)
Dismissal of teachers is an issue in the education system that is related to performance, ethics and organizational needs. This process can occur for certain reasons, such as violations of the code of ethics, inability to meet performance standards, or restructuring of educational institutions. This research aims to analyze the factors that cause teacher dismissal, their impact on educational institutions, and their implications for teachers and students. Apart from that, the legal and ethical aspects that must be fulfilled in the dismissal process are also discussed. With a qualitative approach, this research highlights the importance of fair, transparent and regulatory mechanisms in dealing with teacher dismissals, so as to maintain a balance between institutional needs and the rights of teaching staff. It is hoped that these findings will become a reference for policy makers in creating a professional and sustainable educational environment.